Entrepreneurs in the making: indigenous entrepreneurship and the governance of hope in Chile. Issue 3 (2nd September 2018) - Di Giminiani, Piergiorgio
ABSTRACT: Over the last three decades, national governments and international agencies have introduced a growing number of entrepreneurial programs as a panacea for problems of economic precariousness and exclusion. This article illustrates some of the effects of entrepreneurial discourses and state actions among Mapuche rural residents in Chile. I argue that becoming an entrepreneur is an open-ended process in which state-supported microenterprises consolidate imaginaries of individual self-realization and ethnic autonomy while effectively establishing new bonds of dependence with state and market actors. The effects of entrepreneurial discourses and state actions examined in this article constitute a type of power formation that I define as a 'governance of hope.' This term refers to a disputed political field in which hope is at once an object capitalized by the state apparatus and a source of critical knowledge about ethnic hierarchies within indigenous populations.